Qanun and Syariah Tourism in the Approach of Communication in Central Aceh - Nurliana, Nurliana; Rambe, Elismayanti (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
Explaining the communication used by the Central Aceh Regency Government in providing understanding to tourism actors and tourists about Qanun No. 8 of 2013 and the application of Sharia tourism in tourist areas in Central Aceh is very important. For this reason, this research aims to examine how the tourism Qanun is implemented in Central Aceh, then look at the challenges and opportunities for Central Aceh in implementing Sharia tourism based on the Qanun, as well as the role of communication in it. The research method used in this research is a qualitative method with an exploratory approach. Data is presented according to facts that occur in the field and is organized and systematic. The research results show that to implement Sharia tourism, the Regional Government and Tourism Office use several communication approaches, such as educational campaigns, religious counseling, collaboration with ulama and religious figures, digital marketing, training tour guides, providing free food products, and promoting local culture. Most of the tourist areas in Central Aceh have implemented Sharia tourism in accordance with the Qanun issued by the Aceh Government. Although there are still several obstacles to implementing Sharia tourism in Central Aceh, the communication approach used has succeeded in increasing the number of tourists. Menjelaskan tentang komunikasi yang digunakan Pemerintah Kabupaten Aceh Tengah dalam memberikan pemahaman kepada pelaku wisata dan wisatawan tentang Qanun No 8 tahun 2013 dan penerapan Syariah Tourism pada kawasan wisata di Aceh Tengah merupakan hal yang sangat penting. Untuk itu penelitian ini bertujuan untuk meneliti bagaimana implementasi Qanun pariwisata di Aceh Tengah, kemudian untuk melihat tantangan serta peluang bagi Aceh Tengah dalam menerapkan Syariah Tourism berdasarkan Qanun, serta bagaimana peran komunikasi di dalamnya. Metode penelitian yang digunakan pada penelitian ini adalah metode kualitatif dengan pendekatan eksploratif, data disajikan sesuai fakta yang terjadi di lapangan, terorganisir serta sistematis. Hasil penelitian menunjukkan bahwa untuk menerapkan Syariah Tourism Pemerintah Daerah dan Dinas pariwisata menggunakan beberapa pendekatan komunikasi seperti kampanye edukasi, penyuluhan agama, kolaborasi dengan ulama serta tokoh agama, pemasaran digital, pelatihan pemandu wisata , menyediakan produk makanan secara gratis, dan Promosi Budaya Lokal. Sebagian besar daerah wisata di Aceh Tengah telah menerapkan Syariah Tourism sesuai dengan Qanun yang telah diterbitkan oleh Pemerintah Aceh walaupun masih ada beberapa hal yang menjadi kendala dalam pelaksanaan Syariah Tourism di Aceh Tengah, namun pendekatan komunikasi yang digunakan berhasil meningkatkan jumlah wisatawan.